The Effective Method of Monitoring Visceral Organ Fatty Infiltration Changes After Bariatric Surgery: Ideal IQ Sequence - Yavuz METİN; Nurgül Orhan METİN; Süleyman KALCAN; Muhammed Kadri ÇOLAKOĞLU; Filiz TAŞÇI; Oğuzhan ÖZDEMİR; Ali KÜPELİ (Namık Kemal Tıp Dergisi, 2022)

(untitled)
Aim:The aim of this study is to demonstrate the efficiency of non-invasive imaging method-MR proton density fat fraction (PDFF); ideal IQ sequence- on detecting the effects of bariatric surgery on liver and pancreatic fatty infiltration.Materials and Methods:Thirty-nine patients (25 females, 14 males) who underwent bariatric surgery between May 2016 and April 2017 were analyzed retrospectively in this study. Body mass index (BMI) and body weight (BW) values of all patients were noted one week before and one month after bariatric surgery, and meanwhile an unenhanced upper abdominal MR imaging was performed. Liver fat fraction (LFF), pancreas fat fraction (PFF), liver volume (LV) and craniocaudal length of liver (LL) were measured with MR-PDFF and T2 weighted images. Changes in all parameters after the surgery were recorded and the correlation of these changes with the change in LFF was analyzed.Results:At the end of first month of bariatric surgery, a significant decrease on mean values of LFF and PFF has been observed along with a decrease of LV, LL, BW and BMI (p<0.0001). A moderate positive linear correlation was observed between LFF and PFF, LV, LL (r=0.69, 0.61, 0.49; respectively) while a weak positive linear correlation was noticed between LFF and BMI, BW (r=0.34, 0.21; respectively).Conclusion:Ideal IQ sequence enables quantitative analysis of fatty infiltration of the liver and pancreas and thus may be used as a non-invasive tool to monitor the positive effects of the bariatric surgery on fatty infiltration of these visceral organs in the postoperative period.